Travel Writing for Tourism and City Branding - Mansfield, Charlie,Potočnik Topler, Jasna (Taylor & Francis Group, 2022)
Cover – Half Title – Title Page – Copyright Page – Table of Contents – List of illustrations – Preface – Introduction: Who is commissioning, producing and reading travel and place writing? – 1 Introducing literary travel writing and place-making – 2 Affect, experience and the literary text – 3 Travel writing in place branding – 4 Value, axiology and written representation of place – 5 Methodologies and practice – 6 Case studies in cooperative travel writing – 7 Evaluating writing for quality and value in mentoring – 8 Conclusions, research futures and management implications – References – Index.
Description based on publisher supplied metadata and other sources
Keywords: City promotion; Branding (Marketing); Travel writing; Electronic books